Sabendo q An= A1+(n-1)r, calcule o valor de N em função de An,A1 e r .
Soluções para a tarefa
Respondido por
28
É só tirar e deixar o N sozinho em um canto!!!
![an = a1 + r(n-1) \\ an = a1 + rn -r \\ an - a1 + r = rn \\ n = \frac{an - a1 + r}{r} \\ n = \frac{an-a1}{r} + \frac{r}{r} \\ n= \frac{an-a1}{r} + 1 an = a1 + r(n-1) \\ an = a1 + rn -r \\ an - a1 + r = rn \\ n = \frac{an - a1 + r}{r} \\ n = \frac{an-a1}{r} + \frac{r}{r} \\ n= \frac{an-a1}{r} + 1](https://tex.z-dn.net/?f=an+%3D+a1+%2B+r%28n-1%29+%5C%5C+an+%3D+a1+%2B+rn+-r+%5C%5C+an+-+a1+%2B+r+%3D+rn+%5C%5C+n+%3D+%5Cfrac%7Ban+-+a1+%2B+r%7D%7Br%7D+%5C%5C+n+%3D+%5Cfrac%7Ban-a1%7D%7Br%7D+%2B+%5Cfrac%7Br%7D%7Br%7D+%5C%5C+n%3D+%5Cfrac%7Ban-a1%7D%7Br%7D+%2B+1)
Perguntas interessantes
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Inglês,
1 ano atrás
Biologia,
1 ano atrás